2015
DOI: 10.1590/2179-8087.071714
|View full text |Cite
|
Sign up to set email alerts
|

Telas de Sombreamento e Substratos na Produção de Mudas de Dipteryx alata Vog.

Abstract: RESUMOEste trabalho avaliou tecnologias de ambientes protegidos e substratos para a produção de mudas de Dipteryx alata Vog. Foram utilizados dois ambientes protegidos: telado agrícola, fechamento em 90° graus, com tela preta nas laterais e aluminizada na cobertura, ambas de 50% de sombreamento; telado agrícola, fechamento em 45° graus, com tela preta nas laterais e cobertura, de 50% de sombreamento. Em cada ambiente foram testados substratos de mistura de esterco bovino (E) e vermiculita (V): 100% E + 0% V; 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 13 publications
5
25
0
17
Order By: Relevance
“…Better Acrocomia Aculeata seedlings were observed in Aluminet ® , when compared to Sombrite ® and to the greenhouse with low density polyethylene (Costa et al, 2014). However, Costa et al (2012b) did not find differences between the Sombrite ® and Aluminet ® , both with better results than in the agricultural greenhouse for 'baruzeiro' seedlings (Dipteryx alata), diverging from Costa et al (2015) who reported better baruzeiro seedlings in Sombrite ® compared to Aluminet ® . The amount of photo-assimilates available to be used in the vegetable grown in relation to dry matter mass in the different organs, receives direct influence of the environmental conditions.…”
Section: Sd (Mm)mentioning
confidence: 70%
See 2 more Smart Citations
“…Better Acrocomia Aculeata seedlings were observed in Aluminet ® , when compared to Sombrite ® and to the greenhouse with low density polyethylene (Costa et al, 2014). However, Costa et al (2012b) did not find differences between the Sombrite ® and Aluminet ® , both with better results than in the agricultural greenhouse for 'baruzeiro' seedlings (Dipteryx alata), diverging from Costa et al (2015) who reported better baruzeiro seedlings in Sombrite ® compared to Aluminet ® . The amount of photo-assimilates available to be used in the vegetable grown in relation to dry matter mass in the different organs, receives direct influence of the environmental conditions.…”
Section: Sd (Mm)mentioning
confidence: 70%
“…In this substrate (S6) is observed higher amount of manure than in substrates S4, S12 and S13 (Table 1) with higher nutrients (Table 2) which allowed greater accumulation of mass in the shoot dry mass of the achachairu seedlings. Some studies do not recommend using more than 30% of cattle manure in substrates for some species; other authors recommend no more than 10 or 20%, such as Costa et al (2015) for baruzeiro, Dias et al (2009b) and Silva et al (2009) for mangabeira, Dias et al (2009a) for coffee plant, a fact not verified for achachairu that was adequately adapted to substrates containing up to 50% of cattle manure.…”
Section: Sd (Mm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Dipteryx alata Vog. seedlings, for example, have a lower dry matter yield in substrates with a higher proportion of cattle manure (Costa et al 2015), the same happening for Hancornia speciosa seedlings (Dias et al 2009).…”
Section: Resultsmentioning
confidence: 87%
“…According to Carneiro [14], this is a nondestructive and easily measured feature standing as a parameter for transplanting seedlings into et al [15] and [6], PH cannot be used alone to determine seedling quality and should be used join stem diameter and aerial part biomass to do The number of leaves (NL) had an average of 9.6 leaves in all applied treatments (Fig. 7).…”
Section: Iod In Colatina Espírito Santomentioning
confidence: 99%